Analisis Kadar Logam Berat Timbal (Pb) Dan Cadmium (Cd) Pada Ikan Mujair (Oreochromis Mossambicus) Di Sungai Tambak Oso Kecamatan Waru Kabupaten Sidoarjo Dan Implementasinya Sebagai Bahan Ajar Materi Pencemaran Lingkungan Di SMA - Nurul Islami; Yuni Gayatri (PEDAGO BIOLOGI, 2018)
Abstract : This research aims (1) to know the content of Metal Pb and Cd on Mujair Fish (2) to know the consumption feasibility of Mujair Fish based on the quality SNIÂ  7387:2009; (3) Implementing the research result on Biology teaching material of SMA. This research was qualitative with ex post facto method. This research was done on January to July 2017 in of Tambak Oso River at Waru sub district Sidoarjo regency and tested in BBLK Surabaya. Data collecting technique by taking sample of Mujair fish in Tambak Oso River. The subject of this research were Mujair fish (Oreochromis mossambicus) while the research object were the heavy metal Pb and Cd. The technique sampling was purposive sampling. The analysis technique by comparing the research result and the standard quality of SNI 7387:2009 about maximum limit of heavy metal contamination in food. The results showed that heavy metal content in mujair fish in Tambak Oso River Waru Sub district, Sidoarjo regency, ranging from 0.027-0.041 ppm for heavy metal content and ranging from 0.001 to 0.012 ppm for heavy metal content Cd. These results indicate that mujair fish is still feasible to be consumed because it is still below the quality standard based on SNI 7387: 2009. The results of this study can be made of teaching materials in the form of brochures of heavy metal pollution.